Efektivitas Penyuluhan Literasi Keluarga dalam Meningkatkan Peran Orang Tua pada Pengembangan Literasi Anak Usia Dini - Sinta Wahyuni; Nancy Sofiani; Nafizah (Kilau Publishing, 2026)
Early childhood literacy is an important foundation for cognitive development and educational success. However, parents’ understanding of the role of family literacy is still limited. This community service activity aims to improve parents’ knowledge and awareness of the importance of their involvement in developing children’s literacy. The partners in this activity were members of the community at the Car Free Day (CFD) area of GOR H. Agus Salim, Padang, with the main target being parents with early childhood-aged children, involving a total of 14 active participants. The method used was simple educational outreach through the distribution of brochures (leaflets), accompanied by brief explanations and question-and-answer sessions. The results of the activity showed an increase in parents’ understanding, awareness, and motivation to implement literacy activities at home, such as shared reading and interactive communication. These findings are supported by studies indicating that the family literacy environment significantly influences children’s language development and school readiness. Therefore, family literacy outreach through brochure-based education is effective as an effort to empower communities in improving the quality of early childhood education